1994
DOI: 10.1007/bf03010932
|View full text |Cite
|
Sign up to set email alerts
|

Different priming techniques, including mivacurium, accelerate the onset of rocuronium

Abstract: (73 (57-90) sec) or mivacurium (58 (47-69) sec) were similar to those after succinylcholine (54 (40-68) sec), and were shorter (P < 0.01)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
6

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 23 publications
2
32
0
6
Order By: Relevance
“…In addition, propofol was reported to produce significant depression of laryngeal reflexes 11 . In the previous studies, Griffith et al 6 and Yavascaoglu et al 9 induced anaesthesia with midazolam, fentanyl and propofol and also used 60% N20 in oxygen until tracheal intubation and additional doses of thiopentone 8 or propofol 9 were used as needed prior to tracheal intubation. On the other hand, in this study, we used thiopental sodium, the commonly used induction agent in our country and neither additional dose of TPS nor any inhalational agent except oxygen was used prior to tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, propofol was reported to produce significant depression of laryngeal reflexes 11 . In the previous studies, Griffith et al 6 and Yavascaoglu et al 9 induced anaesthesia with midazolam, fentanyl and propofol and also used 60% N20 in oxygen until tracheal intubation and additional doses of thiopentone 8 or propofol 9 were used as needed prior to tracheal intubation. On the other hand, in this study, we used thiopental sodium, the commonly used induction agent in our country and neither additional dose of TPS nor any inhalational agent except oxygen was used prior to tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…They found that priming with a threeminute interval shortened the onset time of rocuronium irrespectively of the dosage, while a two-minute priming interval did not significantly decrease the onset time. Naguib et al 9 could also demonstrate that priming three minutes prior to an intubation dose significantly shortened the onset time at the AP.…”
Section: Objectifmentioning
confidence: 93%
“…Priming with rocuronium has been shown to shorten onset of neuromuscular blockade (NMB) at the AP. [6][7][8][9] The laryngeal muscles are important because they play a pivotal role in airway maintenance and protection. We know that the time course and potency of muscle relaxants differ at the laryngeal muscles as compared with the AP.…”
Section: Objectifmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results are unequivocal and sometimes even contradictory regarding the interaction among various neuromuscular agents, that is, whether they are additive or synergistic. Structurally dissimilar neuromuscular blocking drugs were shown to result in a potentiating effects as seen with combination of rocuronium and mivacurium [11][12][13][14][15][16][17], rocuronium and cis-atracurium [18,19], and mivacurium and pancuronium [20][21][22]. It was earlier proposed that combinations of structurally similar neuromuscular blocking drugs produce an additive response in humans.…”
Section: Discussionmentioning
confidence: 99%